Investigating factors influencing cross-cultural adjustments of academic expatriates in Malaysia - Nur Amelia Hanah, Hisham (2022)
This study examines the subjective experiences of academic expatriates who have taken tenure at Universiti Utara Malaysia (UUM) and Universiti Malaysia Perlis (UNIMAP). It is intended to bring to the fore the importance of these expatriate experiences in an international human resource management context in academic institutions. By utilising a new proposed framework, the study was conducted to determine factors that may have affected and contributed to the respondents’ personal and professional experiences at their respective institutions, which lead to cross-cultural adjustments. A sample of 18 academic expatriates from both universities in the northern region of Malaysia was interviewed to investigate the relationship between the aforementioned variables in general, their interaction, and work adjustments. The expatriates' experiences were analysed and discussed using a qualitative research methodology. Various personal and professional factors that contributed to the successful tenure of academic expatriates were discovered and further elucidated. The expatriation’s impact on the expatriates, their families, and their careers has been examined in this study. Recognition was given to the uniqueness of such subjective experiences and the contextual factors impacting upon them. The main finding of the research reveals that despite the anxieties posed by the challenges of the ‘unfamiliarity’, academic expatriates with Promethean personalities (Strong Mind-Set, Positive Attitudes, Flexible, Adaptive, etc.) would survive better and progress well. Also, academic expatriates that take social initiative acclimatise more readily to their fresh social environment, which improves their work performance. The findings also suggested the need for both universities to develop adjustment programmes that would assist the expatriation process in providing insights and skills that could empower the individual to achieve true personal fulfilment in the pursuit of career success.